2020
DOI: 10.3389/fpsyg.2020.00028
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Career Social Support and Employability of College Students: A Moderated Mediation Model

Abstract: This study examines the underlying mechanism that connects career social support with employability through a survey of 392 Chinese college students. The results showed that career social support had a positive effect on career adaptation and employability of college students, and career adaptation mediated the association between career social support and employability. Furthermore, proactive personality was found to play a moderating role in linking career adaptation and employability. More specifically, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…This implies that desirable attributes can offer students more opportunities to take advantage of their strengths to develop their ability to obtain and retain a job, revealing the contingent role of proactive personality in employability from a theoretical perspective. These findings are consistent with previous research, which has shown that individuals with high initiative tend to create conditions for themselves to play to their strengths and pursue career goals set by themselves, which in turn has some positive effects on improving individual employability (Chughtai, 2019 ; Xia et al, 2020 ). Accordingly, our identification of two moderators with distinct paths increases the understanding of students’ employability by using personal-dependent variables to examine the unique relationship between future orientation and employability among students majoring in tourism and hospitality.…”
Section: Discussionsupporting
confidence: 92%
“…This implies that desirable attributes can offer students more opportunities to take advantage of their strengths to develop their ability to obtain and retain a job, revealing the contingent role of proactive personality in employability from a theoretical perspective. These findings are consistent with previous research, which has shown that individuals with high initiative tend to create conditions for themselves to play to their strengths and pursue career goals set by themselves, which in turn has some positive effects on improving individual employability (Chughtai, 2019 ; Xia et al, 2020 ). Accordingly, our identification of two moderators with distinct paths increases the understanding of students’ employability by using personal-dependent variables to examine the unique relationship between future orientation and employability among students majoring in tourism and hospitality.…”
Section: Discussionsupporting
confidence: 92%
“…As directly stated above, the driving force of social capital towards symbolic capital cannot be underestimated. That relationship seems to be a decisive factor to facilitate how graduates progress their positioning in the job market (Bassey, et al, 2019;Islam, 2018;Xia et al, 2020). Based on the participants' perspectives, they understood themselves in response to their varying sociocultural contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Acting as an independent variable in the examined relationships between forms of capital, economic capital referred to students' financial strengths that assisted students to access learning resources. Social capital suggested students' attempted to expand their personal network and professional connections with those who supports mutually on various purposes (Islam, 2018;Xia et al, 2020), while cultural capital indicated cultural knowledge and understanding that enabled learners to assimilate and integrate into other diverse settings in which they live or work (Bahna, 2017;Pham et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations